Distribution, transportation, and coordination in African indigenous vegetables value chains: A scoping review - Alulu, Joseph; Makyao, Mary; Huyskens-Keil, Susanne; Lenz, Barbara; Muendo, Kavoi M.; Mganilwa, Zacharia; Mbeche, Robert; Mgaya, Prosper; Mithöfer, Dagmar (Frontiers in Environmental Economics, 2023)
Malnutrition continues to be a major problem with negative implications on economic and human development in many parts of the world, including in Sub-Saharan Africa (SSA). Strengthening promising underutilized crops that are nutrient dense, climate resilient, and locally adaptable is an instrumental approach to enhancing dietary diversity. Due to their nutritional and economic benefits, African Indigenous Vegetables (AIVs) have the potential to contribute to livelihoods and address challenges of food and nutrition insecurity. Despite their importance but due to their perishability, AIVs tend to suffer from high post-harvest losses (PHLs). Effective distribution systems along the value chain have the potential to reduce PHLs for AIVs. We therefore conducted a scoping review on transport systems and coordination in AIVs value chains in SSA. The objectives of this review were to summarize and analyze the focus of research in AIVs transport, to analyze the extent to which the literature synthesizes interactions of sub-components of the chains, and to identify knowledge gaps in AIVs transport literature. Based on the research foci, we categorize the reviewed articles into seven themes. Our analyses indicate that distance to agricultural market is a fundamental aspect of AIVs transportation, as it interacts with transport costs, market participation, produce quality, and profit efficiency. Results show that collective action is instrumental in the coordination of AIVs transportation and that it contributes to cost reduction. Following light exploration of determinants of choice of means of transport, we recommend further research in this area for improvement of transportation in AIVs value chains.